2008
DOI: 10.1177/0022466908320461
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Ethnic Disproportionality in Special Education in an English Population

Abstract: Differences in the proportion of students identified as having Special Educational Needs (SEN) across different ethnic groups has historically been of concern both in the UK and US. However the absence of student level data has hindered the investigation of the reasons for such disproportionality. This paper presents an analysis of the 2005 Pupil Level Annual School Census for 6.5 million students aged 5-16 in England. Logistic regression analyses were completed to calculate the odds-ratios of having an identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 33 publications
5
89
0
7
Order By: Relevance
“…There was also a significant relationship between SLCN and social disadvantage: children with high socioeconomic disadvantage were 2.30 times more likely to have SLCN than children with low levels of socioeconomic disadvantage. This social gradient of SLCN is well established and is not unique to SLCN: other research has indicated a strong association with, for example, MLD and BESD (Strand and Lindsay, 2009). …”
Section: Prevalencementioning
confidence: 83%
See 3 more Smart Citations
“…There was also a significant relationship between SLCN and social disadvantage: children with high socioeconomic disadvantage were 2.30 times more likely to have SLCN than children with low levels of socioeconomic disadvantage. This social gradient of SLCN is well established and is not unique to SLCN: other research has indicated a strong association with, for example, MLD and BESD (Strand and Lindsay, 2009). …”
Section: Prevalencementioning
confidence: 83%
“…LI is also more prevalent among children from more socially disadvantaged backgrounds (Department for Education, 2015). The relationship between LI and ethnicity or race is less well researched, but Strand and Lindsay (2009) report that Chinese, Bangladeshi, Black African, Black Caribbean, and Black other children were overrepresented for SLCN compared with White British children.…”
Section: Prevalence Of Language Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…These include both large scale studies of general populations of children, indicating the very powerful effects of socioeconomic disadvantage (Strand, 2014), parenting (Kiernan and Mensah, 2011), and school effects (Teddlie and Reynolds, 2000;Strand, 2016), which shape children's opportunities for optimal development; and also analyses of total populations of children with a range of SEN, particularly with respect to social disadvantage (Strand and Lindsay, 2009;Department for Education, 2016b).…”
mentioning
confidence: 99%